Thermal‐Triggered Dynamic Disulfide Bond Self‐Heals Inorganic Perovskite Solar Cells. Issue 8 (11th January 2022) - Zhang, Qiaoyu; Duan, Jialong; Guo, Qiyao; Zhang, Junshuai; Zheng, Dengduan; Yi, Fangxuan; Yang, Xiya; Duan, Yanyan; Tang, Qunwei
Abstract: One great challenge for perovskite solar cells (PSCs) lies in their poor operational stability under harsh stimuli by humidity, heat, light, etc. Herein, a thermal‐triggered self‐healing polyurethane (PU) is tailored to simultaneously improve the efficiency and stability of inorganic CsPbIBr2 PSCs. The dynamic covalent disulfide bonds between adjacent molecule chains in PU at high temperatures self‐heal the in‐service formed defects within the CsPbIBr2 perovskite film. Finally, the best device free of encapsulation achieves a champion efficiency up to 10.61 % and an excellent long‐term stability in an air atmosphere over 80 days and persistent heat attack (85 °C) over 35 days. Moreover, the photovoltaic performances are recovered by a simple heat treatment. Abstract : A functionalized polyurethane is used as an additive to self‐heal a CsPbIBr2 film by a disulfide‐exchange reaction upon heat treatment. The inorganic CsPbIBr2 perovskite solar cell achieves a champion efficiency of 10.61 % with efficiency recovery after heat treatment.